2011
DOI: 10.1111/j.2044-8325.2010.02013.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in burnout: A 10-year follow-up study among primary care physicians

Abstract: The aim of the present study is (1) to investigate the impact of patient demands on primary care physicians’ burnout and (2) to examine the stability and change of burnout across time. Participants were drawn from the official Dutch registration system for primary health care, and longitudinal panel data (n= 165) from three waves with a 5‐year time interval were used. They filled in the Maslach Burnout Inventory (MBI) and a validated scale for the assessment of patient demands. The results of various stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 65 publications
7
97
2
5
Order By: Relevance
“…Third, we found that the stability of burnout was higher (40-45%) in this study than that observed by Schaufeli et al (2011), who used a similar stability and change model and revealed that about one quarter was accounted for by a stable component. The reasons for this might lie on the one hand in the larger time intervals (5 years in their study versus 1 year in our study) and on the other hand in the operationalization of burnout.…”
Section: Accepted M Manuscriptcontrasting
confidence: 54%
See 1 more Smart Citation
“…Third, we found that the stability of burnout was higher (40-45%) in this study than that observed by Schaufeli et al (2011), who used a similar stability and change model and revealed that about one quarter was accounted for by a stable component. The reasons for this might lie on the one hand in the larger time intervals (5 years in their study versus 1 year in our study) and on the other hand in the operationalization of burnout.…”
Section: Accepted M Manuscriptcontrasting
confidence: 54%
“…The employees' actual levels of job demands, job resources, and well-being are assumed to be the sum of two independent components: (1) a component reflecting the time-invariant stability, and (2) a component reflecting occasional changes. Therefore, the variances of the observed scores are partitioned into a stable component that is determined by stable personal and/or environmental characteristics and that -by definition -does not change across time, and a change component that is characterized by changes within the working environment and that -by definition -does change across time (Cole et al, 2005;Schaufeli et al, 2011).…”
Section: The Present Studymentioning
confidence: 99%
“…resource allocation, improved patient care and health outcomes, and reduced burnout in primary care clinicians. [23][24][25][26][27][28] Primary care physicians (PCPs) have a unique perspective on the relative level of effort required to care for patients in their panel, including both visit-based and non-visit-based work, as well as patients' psychosocial needs that affect primary care team effort. We previously evaluated a measure of patient complexity using physician qualitative assessments.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980's burnout was described as dynamic process. Currently it is considered as a state characterized by chronicity and persistence (Schaufeli et al, 2011), therefore burnout is defined as an enduring, negative state connected with work which occurs in case of people that are generally healthy. The syndrome of burnout is marked with exhaustion that is accompanied with psychical and physical discomfort, the feeling of diminished effectiveness, lowered motivation, and disfunctional attitudes and behaviours at work.…”
Section: Literature Reviewmentioning
confidence: 99%